Verso una ricerca identitaria al femminile in “L’età del malessere” di Dacia Maraini - Zoubeida OUCHTATI (Altralang Journal, 2020)
ABSTRACT: Writing allows the woman to express herself and talk about her life by emphasizing her interiority. Unlike the other female literatures (English or French for example), the Italian one has been for a long time put in the shadow of “men”. In Italy, the interest in the writing of women was born in the second half of the twentieth century thanks to the feminist movement and the feminine literary criticism. In this article, we study “L’età del malessere”; a novel written by Dacia Maraini who is one of the most known Italian feminists and intellectuals. The main purpose of this study is to show how Dacia Maraini manages to deal with the theme of female identity through her protagonist “Enrica”. The writer highlights both the family and the social context in which Enrica grows because they affect the process of building her identity. Eventually, Enrica gains her identity by gaining her freedom after various vital and bodily experiences.